A diaphragm, a multi-layer composite membrane structure, a sensor and a microphone
By using graphite and/or carbon -shaped aliens in the vibration membrane, combined with the front -drive body thermal solution synthesis technology, the existing graphene film preparation is complicated, and high -performance, low -cost acoustic and sensors are achieved Device.
Patent Information
- Application Number
- CN202410887978.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-04
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-04
AI Technical Summary
The preparation process of existing graphene diaphragms is complicated, resulting in cumbersome process, high cost and poor performance consistency, making it difficult to show obvious advantages in the fields of acoustics and sensors.
The use of graphite and/or carbon -alien body, synthesize the vibration membrane through the thermal solution method of the front drive body to ensure that the two -dimensional chip -shaped carbon grain structure is unfolded in the vibration direction of the vibration film. There is a diaphragm with a variety of opposite sex.
The high Yang's modulus, excellent conductivity and thermal conductivity of the high -yang family, improve the sensitivity and frequency response range of the microphone, reduce production costs and improve process consistency.
Smart Images

Figure CN118574064B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of diaphragms for sound generation, and in particular to a diaphragm, a multi-layer composite membrane structure, a pressure sensor, an airflow sensor and a microphone. Background Art
[0002] The diaphragm plays a vital role in acoustic and pressure sensors and transmitters. The diaphragm's physical properties such as conductivity, Young's modulus, density, and acoustoelastic attenuation coefficient determine the performance limits of the final product.
[0003] Patent CN106937229A and Patent CN108955860B both propose a microphone using a graphene diaphragm. Since graphene is used as the core mechanical structure of the diaphragm, the sensitivity of the microphone is significantly improved, the maximum tolerable sound pressure characteristics of the microphone are improved, and a wider frequency response characteristic is obtained.
[0004] However, the preparation process of the single-layer or multi-layer graphene used in this scheme is relatively complicated. The commonly used graphene film preparation methods such as chemical vapor deposition, filtration, spraying and other methods have complicated preparation processes. Whether compared with the existing electret microphone diaphragm or silicon micro-microphone diaphragm, its comprehensive performance and cost ratio are difficult to have obvious advantages.
[0005] Patent CN117177140A provides a composite diaphragm structure. By controlling the material combination of the diaphragm at different positions, a diaphragm with different stiffness characteristics in different areas is obtained, thereby further optimizing the microphone characteristics or speaker characteristics based on the diaphragm to obtain better acoustic characteristics.
[0006] However, the non-uniform stiffness distribution of the diaphragm is achieved by compounding different layers of elastic materials at different positions of the diaphragm. The processing method is cumbersome and requires processing at least three layers of elastic body. The processing deviation of each layer of elastic body affects the stiffness of the composite part, so the final diaphragm performance consistency is poor. The process is complicated and the production cost is high.
[0007] Utility model CN219068364U provides a composite diaphragm structure with a graphene layer, wherein the diaphragm structure comprises: a first polysilicon layer, at least one graphene layer, and a second polysilicon layer stacked in sequence; wherein the first polysilicon layer, the graphene layer, and the second polysilicon layer all have a corrugated structure, and the corrugated structures of the first polysilicon layer, the graphene layer, and the second polysilicon layer are stacked in sequence. The utility model can simultaneously improve the sensitivity and reliability of the diaphragm structure.
[0008] However, the above-mentioned utility model adopts an intermediate metal layer as a transition and catalyst, and the preparation process of graphene is complicated. The processing technology of multi-layer graphene and polysilicon layer will greatly reduce the production process consistency of the overall diaphragm. Therefore, although the performance of the monomer will be improved, its parameter distribution range will increase, and the overall parameter performance fluctuation will become larger. Moreover, due to the complex processing technology, the high production cost also limits the competitiveness of this solution. Summary of the invention
[0009] The present invention provides a diaphragm, a multi-layer composite membrane structure, a pressure sensor, an airflow sensor and a microphone, which are used to solve the technical problems existing in the above-mentioned prior art.
[0010] To achieve the above-mentioned purpose, the present invention provides a diaphragm, which includes graphite and / or other allotropes of carbon, wherein a portion of the graphite inside the diaphragm has a first characteristic, the first characteristic being that the two-dimensional flaky carbon grain structure inside the diaphragm is expanded in the vibration direction of the diaphragm or the force-bearing direction of the diaphragm and the expansion direction of the two-dimensional flaky carbon grain structure is perpendicular to the movement direction of the diaphragm, the graphite inside the diaphragm has a low porosity characteristic, and the apparent density of the graphite inside the diaphragm is between 1.5 g / cm³ and 2.2 g / cm³.
[0011] In an embodiment of the present invention, the average thickness of the diaphragm is between 0.1 μm and 0.1 mm.
[0012] In one embodiment of the present invention, the diaphragm is synthesized by precursor pyrolysis method, and the process is as follows:
[0013] S1: manufacturing a precursor into a planar film, wherein the precursor is a raw material for manufacturing the planar film;
[0014] S2: placing the planar film in an oxygen-free environment with controllable temperature and pressure for heating, and sequentially performing the following steps S21 to S23:
[0015] S21: carbonization process, volatile organic matter and small molecular components in the planar film evaporate;
[0016] S22: Pyrolysis process, the chemical bonds between nitrogen, hydrogen, oxygen and carbon in the long-chain molecules in the planar film are broken, and gas overflow is generated;
[0017] S23: graphitization process, the carbon elements in the planar film form graphitized grains;
[0018] S3: post-processing, including stamping and rolling to adjust thickness;
[0019] S4: Diaphragm preparation is completed.
[0020] In one embodiment of the present invention, the precursor is an organic material, the precursor molecule includes long-chain carbon or long-chain benzene ring and the mass proportion of carbon element therein is greater than 30%.
[0021] In one embodiment of the present invention, the precursor is first manufactured into the thickness and shape required by the diaphragm, and then step S2 is performed; or
[0022] First, the precursor is manufactured into the intermediate shape required by the diaphragm, and then step S2 is performed, and then it is further processed to obtain the final required diaphragm shape.
[0023] In one embodiment of the present invention, the diaphragm is synthesized by pyrolysis, which is to pyrolyze and deposit the precursor gas on a pre-processed solid surface under a pre-set platform; or
[0024] The diaphragm is formed by a vapor deposition method.
[0025] The present invention also provides a multi-layer composite membrane structure, which includes the above-mentioned diaphragm.
[0026] The present invention also provides a pressure sensor, which comprises the above-mentioned diaphragm.
[0027] The present invention also provides an airflow sensor, which comprises the above-mentioned diaphragm.
[0028] The invention also provides a microphone, which comprises the diaphragm.
[0029] The present invention has the following beneficial technical effects:
[0030] (1) The diaphragm of the present invention has strong anisotropy at the macroscopic level, which is similar to the properties of graphene to a certain extent, and therefore has many advantages possessed by graphene diaphragms.
[0031] (2) The diaphragm of the present invention is composed of many small-sized two-dimensional graphite structures arranged relatively evenly at the microscopic level, so its apparent density is significantly lower than that of graphene (2.267g / cm³). Unlike graphene, the diaphragm of the present invention is insensitive to local lattice defects, and lattice defects will not have a significant impact on mechanical or electrical properties. In addition, the diaphragm of the present invention is easy to prepare by a variety of methods, the process method is flexible, easy to mass produce, and has a high process consistency.
[0032] (3) The diaphragm of the present invention has relatively excellent mechanical properties, with a high Young's modulus, and excellent electrical and thermal conductivity. Therefore, when used as the main component of an acoustic diaphragm, it can achieve higher microphone sensitivity and a wider frequency response range; it can also achieve a loudspeaker with a higher output sound pressure level, or a pressure and airflow sensor with better linearity and higher sensitivity.
[0033] (3) When the diaphragm of the present invention is manufactured by the precursor pyrolysis method, since the precursors are mostly organic substances with high carbon content, such as polymer plastics, pulp, cellulose, polyimide, acrylic fiber, nylon, etc., these organic substances have soft and plastic properties under specific conditions, and are easy to be precisely formed into the required shape. For example, cellulose and pulp are very easy to shape under wet conditions, and various thermoplastic plastics such as polyimide and nylon can have good plasticity at higher temperatures.
[0034] (4) When the diaphragm of the present invention is manufactured by pyrolysis, hot pressing or vapor deposition, the deposition surface thereof can also be pre-formed by a die-casting mold to obtain the final three-dimensional structure of the diaphragm.
[0035] (5) The present invention forms the diaphragm into a three-dimensional structure, or adds features such as reinforcing beams, reinforcing ribs, slots, holes, protrusions, folds, and corrugations to the shape of the diaphragm, thereby adjusting the stiffness of the diaphragm at different positions, thereby obtaining excellent acoustic characteristics.
[0036] The microphone based on the above diaphragm has higher sensitivity and dynamic range, and lower harmonic distortion. The loudspeaker based on the diaphragm has higher output sound pressure level and lower total harmonic distortion characteristics. The pressure or airflow sensor based on the diaphragm has better sensitivity.
[0037] At the same time, the present invention has a simple processing method, so the processing cost is low. In addition, through the process composition parameters, such as temperature, temperature change rate and other basic process characteristics, the mechanical and acoustic properties of the final diaphragm can be accurately controlled, thereby obtaining a higher process consistency.
[0038] In summary, compared with existing solutions, the diaphragm and the preparation method thereof described in the present invention can be used to prepare acoustic and sensor devices with better performance and lower cost, and have higher social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1A A schematic diagram of the distribution of crystal grains in an existing graphite diaphragm;
[0041] Figure 1B A schematic diagram of the grain distribution in another existing graphite diaphragm;
[0042] Figure 1C It is a schematic diagram of the grain distribution in the graphite diaphragm of the present invention;
[0043] Figure 1D A schematic diagram showing the high consistency of the two-dimensional flake grains inside graphite;
[0044] Figure 2 is a schematic diagram of a diaphragm according to an embodiment of the present invention;
[0045] Figure 3 A schematic diagram of a diaphragm provided with a three-dimensional structure according to an embodiment of the present invention;
[0046] Figure 4 It is a cross-sectional schematic diagram of an airflow sensor or a microphone manufactured using the diaphragm of the present invention. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Figure 1A Schematic diagram of grain distribution in an existing graphite diaphragm. Figure 1A As shown, the two-dimensional lamellar grains inside the graphite are arranged in a disordered manner. The apparent density of the graphite diaphragm with such characteristics is between 0.001g / cm³ and 0.5g / cm³, and its mechanical strength is good; its typical Young's modulus varies with density between 2MPa (megaPascal) and 1000MPa; its electrical conductivity is good, and the apparent density varies between 1S / cm (Siemens per centimeter) and 200 S / cm; its thermal conductivity is average, and varies with density between 0.5 W / (m·K) (watt per Kelvin meter) and 100 W / (m·K).
[0049] Figure 1A The typical preparation method of the graphite diaphragm shown is the expanded graphite method, that is, by inserting intercalation compounds between the interstices of graphite layer atoms and separating the graphite layers after high temperature treatment. Expanded graphite can be prepared into finished graphite products with different densities and porosities through a variety of post-processing methods, such as crushing, hot pressing, etc.
[0050] Figure 1B Schematic diagram of grain distribution in another existing graphite diaphragm, such as Figure 1BAs shown in the figure, the two-dimensional flake grains inside the graphite are in a certain order, and the whole shows a certain degree of anisotropy, but it still has a lot of disordered arrangement and internal pores. The apparent density of the graphite diaphragm with such characteristics is about 0.5g / cm³ to 1.5g / cm³, its mechanical strength is good, and its typical Young's modulus varies between 1000Pa and 2000Pa depending on the density; its electrical conductivity is good, and the in-plane electrical conductivity varies between 200 S / cm and 1000 S / cm depending on the density; its thermal conductivity is average, and the in-plane thermal conductivity varies with the density and varies between 100 W / (m·K) and 500 W / (m·K).
[0051] Figure 1B The typical preparation method of the graphite diaphragm shown is high-pressure hot pressing. By heating the expanded graphite in a mold and applying high pressure, the two-dimensional lamellar grains in the graphite begin to be arranged in an orderly manner under external pressure. Since the interlayer force of the two-dimensional lamellar grains of graphite is mainly van der Waals force, the layers are connected by weaker forces. Therefore, the consistency of the two-dimensional lamellar grains usually obtained by the hot pressing method is not high, and its overall apparent density is generally less than 1.5 g / cm³.
[0052] Figure 1C Schematic diagram of the grain distribution in the graphite diaphragm of the present invention. Figure 1C As shown in the figure, the two-dimensional flake grains inside the graphite are arranged in an orderly manner with high consistency, and the whole exhibits strong anisotropy. The apparent density of the graphite diaphragm with such characteristics is between 1.5g / cm³ and 2.2g / cm³, and the mechanical strength is excellent, between that of graphite and graphene, with a typical in-plane Young's modulus of about 10GPa; the in-plane electrical conductivity is excellent, with a typical value of about 3000S / cm; the in-plane thermal conductivity is excellent, about 1900 W / (m·K).
[0053] Figure 1D This is a schematic diagram showing the high consistency of the two-dimensional flake grains inside graphite, such as Figure 1D As shown in the figure, the two-dimensional lamellar grains inside the graphite are arranged in an orderly manner with high consistency, showing strong anisotropy as a whole, with only a small amount of pores and defects between the two-dimensional lamellar grains inside the structure. The apparent density of the graphite diaphragm with such characteristics is between 2.2 g / cm³ and 2.267 g / cm³, and the interior is mainly composed of graphene. This highly two-dimensional crystal structure has extremely high mechanical strength, with a typical maximum Young's modulus of about 1000 GPa in the plane; excellent in-plane electrical conductivity, with a maximum of about 1 million S / cm; and excellent in-plane thermal conductivity, with a maximum of about 5200 W / (m·K).
[0054] Figure 1DTypical preparation methods can directly use graphite crystal exfoliation, vapor deposition, epitaxial growth and redox methods to prepare multilayer graphene structures.
[0055] The present invention provides a diaphragm, which includes graphite and / or other allotropes of carbon, wherein a portion of the graphite inside the diaphragm has a first characteristic, the first characteristic being that the two-dimensional flaky carbon grain structure inside the diaphragm is expanded in the vibration direction of the diaphragm or the force-bearing direction of the diaphragm and the expansion direction of the two-dimensional flaky carbon grain structure is perpendicular to the movement direction of the diaphragm, the graphite inside the diaphragm has a low porosity characteristic, and the apparent density of the graphite inside the diaphragm is between 1.5 g / cm³ and 2.2 g / cm³.
[0056] Figure 2 FIG. 1 is a schematic diagram of a diaphragm according to an embodiment of the present invention. Figure 2 As shown, the two-dimensional flaky carbon grain structure in the diaphragm is expanded in the vibration direction of the diaphragm and the expansion direction of the two-dimensional flaky carbon grain structure is perpendicular to the movement direction of the diaphragm.
[0057] The diaphragm provided by the present invention has strong anisotropy, which is because it is composed of a plurality of small-sized two-dimensional graphite grains with a relatively uniformly arranged unfolded structure from a microscopic point of view.
[0058] The diaphragm of the present invention may be further provided with a three-dimensional spatial structure, which includes a hollow composite hole, a composite beam or a hollow multi-layered structure. The diaphragm may also be provided with reinforcing beams, reinforcing ribs, grooves, holes, protrusions, folds or corrugations to adjust the stiffness of different positions of the diaphragm, thereby obtaining excellent acoustic properties.
[0059] Figure 3 FIG. 1 is a schematic diagram of a diaphragm provided with a three-dimensional structure according to an embodiment of the present invention. Figure 3 As shown, a ring-shaped beam and a radial support beam are arranged in the middle part of the diaphragm, so as to strengthen the rigidity in the middle part.
[0060] In an embodiment of the present invention, the average thickness of the diaphragm is between 0.1 μm and 0.1 mm.
[0061] In one embodiment of the present invention, the diaphragm is synthesized by precursor pyrolysis method, and the process is as follows:
[0062] S1: manufacturing a precursor into a planar film, wherein the precursor is a raw material for manufacturing the planar film;
[0063] S2: placing the planar film in an oxygen-free environment with controllable temperature and pressure for heating, and sequentially performing the following steps S21 to S23:
[0064] S21: carbonization process, volatile organic matter and small molecular components in the planar film evaporate;
[0065] S22: Pyrolysis process, the chemical bonds between nitrogen, hydrogen, oxygen and carbon in the long-chain molecules in the planar film are broken, and gas overflow is generated;
[0066] S23: graphitization process, the carbon elements in the planar film form graphitized grains;
[0067] S3: post-processing, including stamping and rolling to adjust thickness;
[0068] S4: Diaphragm preparation is completed.
[0069] In one embodiment of the present invention, the precursor is an organic material, the precursor molecule includes long-chain carbon or long-chain benzene ring and the mass proportion of carbon element therein is greater than 30%. The precursor is, for example, cellulose, chitosan, polyimide, nitrile plastic or nylon.
[0070] In one embodiment of the present invention, the precursor is first manufactured into the thickness and shape required by the diaphragm, and then step S2 is performed; or
[0071] First, the precursor is manufactured into the intermediate shape required by the diaphragm, and then step S2 is performed, and then it is further processed to obtain the final required diaphragm shape.
[0072] In one embodiment of the present invention, the diaphragm is synthesized by pyrolysis, which is to pyrolyze and deposit the precursor gas on a pre-processed solid surface under a pre-set platform; or
[0073] The diaphragm is formed by a vapor deposition method.
[0074] The present invention also provides a multi-layer composite membrane structure, which includes the above-mentioned diaphragm.
[0075] The present invention also provides a pressure sensor, which comprises the above-mentioned diaphragm.
[0076] The present invention also provides an airflow sensor, which comprises the above-mentioned diaphragm.
[0077] The invention also provides a microphone, which comprises the diaphragm.
[0078] The diaphragm of the present invention can be used to manufacture airflow sensors or microphones. Figure 4 FIG. 4 is a cross-sectional schematic diagram of an airflow sensor or microphone manufactured using the diaphragm of the present invention. Figure 4As shown, the airflow sensor or microphone is composed of a back plate, a diaphragm, a substrate and an isolation structure therebetween. The diaphragm can be closed or provided with a single or multiple symmetrically or asymmetrically distributed small holes to balance the low-frequency pressure components on both sides of the diaphragm. Openings are provided on the substrate and the back plate so that the input sound pressure signal or airflow pressure signal is applied to both sides of the diaphragm.
[0079] The present invention has the following beneficial technical effects:
[0080] (1) The diaphragm of the present invention has strong anisotropy at the macroscopic level, which is similar to the properties of graphene to a certain extent, and therefore has many advantages possessed by graphene diaphragms.
[0081] (2) The diaphragm of the present invention is composed of many small-sized two-dimensional graphite structures arranged relatively evenly at the microscopic level, so its apparent density is significantly lower than that of graphene (2.267g / cm³). Unlike graphene, the diaphragm of the present invention is insensitive to local lattice defects, and lattice defects will not have a significant impact on mechanical or electrical properties. In addition, the diaphragm of the present invention is easy to prepare by a variety of methods, the process method is flexible, easy to mass produce, and has a high process consistency.
[0082] (3) The diaphragm of the present invention has relatively excellent mechanical properties, with a high Young's modulus, and excellent electrical and thermal conductivity. Therefore, when used as the main component of an acoustic diaphragm, it can achieve higher microphone sensitivity and a wider frequency response range; it can also achieve a loudspeaker with a higher output sound pressure level, or a pressure and airflow sensor with better linearity and higher sensitivity.
[0083] (3) When the diaphragm of the present invention is manufactured by the precursor pyrolysis method, since the precursors are mostly organic substances with high carbon content, such as polymer plastics, pulp, cellulose, polyimide, acrylic fiber, nylon, etc., these organic substances have soft and plastic properties under specific conditions, and are easy to be precisely formed into the required shape. For example, cellulose and pulp are very easy to shape under wet conditions, and various thermoplastic plastics such as polyimide and nylon can have good plasticity at higher temperatures.
[0084] (4) When the diaphragm of the present invention is manufactured by pyrolysis, hot pressing or vapor deposition, the deposition surface thereof can also be pre-formed by a die-casting mold to obtain the final three-dimensional structure of the diaphragm.
[0085] (5) The present invention forms the diaphragm into a three-dimensional structure, or adds features such as reinforcing beams, reinforcing ribs, slots, holes, protrusions, folds, and corrugations to the shape of the diaphragm, thereby adjusting the stiffness of the diaphragm at different positions, thereby obtaining excellent acoustic characteristics.
[0086] The microphone based on the above diaphragm has higher sensitivity and dynamic range, and lower harmonic distortion. The loudspeaker based on the diaphragm has higher output sound pressure level and lower total harmonic distortion characteristics. The pressure or airflow sensor based on the diaphragm has better sensitivity.
[0087] At the same time, the present invention has a simple processing method, so the processing cost is low. In addition, through the process composition parameters, such as temperature, temperature change rate and other basic process characteristics, the mechanical and acoustic properties of the final diaphragm can be accurately controlled, thereby obtaining a higher process consistency.
[0088] In summary, compared with existing solutions, the diaphragm and the preparation method thereof described in the present invention can be used to prepare acoustic and sensor devices with better performance and lower cost, and have higher social benefits.
[0089] Those skilled in the art can understand that the accompanying drawings are only schematic diagrams of an embodiment, and the modules or processes in the accompanying drawings are not necessarily required to implement the present invention.
[0090] Those skilled in the art can understand that the modules in the device in the embodiment can be distributed in the device in the embodiment according to the description of the embodiment, or can be changed accordingly and located in one or more devices different from the embodiment. The modules in the above embodiment can be combined into one module, or can be further divided into multiple sub-modules.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A diaphragm, characterized in that: Including graphite, inside the diaphragm, a part of the graphite has a first feature, the first feature is that the two-dimensional flaky carbon grain structure in the diaphragm is unfolded in a direction perpendicular to the vibration direction of the diaphragm, or the first feature is that the two-dimensional flaky carbon grain structure in the diaphragm is unfolded in the bearing direction of the diaphragm and the unfolding direction is perpendicular to the movement direction of the diaphragm, the two-dimensional flaky carbon grains are arranged in a consistent and orderly manner, the graphite in the diaphragm has a low porosity feature, the apparent density of the graphite in the diaphragm is between 1.5 g / cm³ and 2.2 g / cm³, wherein the diaphragm is synthesized by a precursor pyrolysis method, and the process is as follows: S1, manufacturing a precursor into a planar film, wherein the precursor is a raw material for manufacturing the planar film; S2, placing the planar film in an oxygen-free environment with controllable temperature and pressure for heating, and sequentially performing the following steps S21 to S23; S21, a carbonization process, in which volatile organic matter and small molecular components in the planar film evaporate; S22, a pyrolysis process, in which the chemical bonds between nitrogen, hydrogen, oxygen and carbon in the long-chain molecules in the planar film are broken, and gas overflow is generated; S23, a graphitization process, in which the carbon elements in the planar film form graphitized grains; S3, post-processing, including stamping and rolling to adjust thickness; S4. The diaphragm preparation is completed.
2. The diaphragm according to claim 1, characterized in that: The average thickness of the diaphragm is between 0.1 μm and 0.1 mm.
3. The diaphragm according to claim 1, characterized in that: The precursor is an organic material, the precursor molecule includes long-chain carbon or long-chain benzene ring and the mass proportion of carbon element therein is greater than 30%.
4. The diaphragm according to claim 3, characterized in that: First, the precursor is manufactured into the thickness and shape required by the diaphragm, and then step S2 is performed; or First, the precursor is manufactured into the intermediate shape required by the diaphragm, and then step S2 is performed, and then it is further processed to obtain the final required diaphragm shape.
5. A multi-layer composite membrane structure, characterized in that: The multi-layer composite membrane structure comprises the diaphragm according to any one of claims 1 to 4.
6. A pressure sensor, characterized in that: A diaphragm comprising any one of claims 1 to 4.
7. An airflow sensor, characterized in that: A diaphragm comprising any one of claims 1 to 4.
8. A microphone, characterized in that: A diaphragm comprising any one of claims 1 to 4.
Citation Information
Patent Citations
Capacitive sound acquisition device and microphone
CN106937229A
A high-strength graphene film-based acoustic wave detector
CN108955860B
Vibrating diaphragm, MEMS chip and microphone
CN117177140A
Method of producing a carbon diaphragm for an acoustic instrument
US4221773A